Miss Be, Her Red Threads, and the Others. A Story about Social Justice and the Appreciation of Visual Art in Research Practice - Zimmermann, Anja; Hermsen, Maaike (Murmurations: Journal of Transformative Systemic Practice, 2022)
In 2020, I started to write a PhD proposal. My interest is, how art-based communities can foster social justice for people with intellectual disability/ learning disability. As an art therapist and as a graduate student, I wondered how visual art could be integrated in my research project, if seen from different perspectives. Underlying to the idea of appreciating art in my research project is literature that indicates that art-based approaches are helpful to explore, understand, and transform complex social issues (McNiff, 1998; Barone and Eisner, 2012; Savin-Baden and Wimpenny, 2014; Leavy, 2015; Goopy and Kassan, 2019), and that opportunities of art in research projects are expanding, inviting a clearer, embodied praxis (Bresler, 2006, 2018; Visse, Hansen and Leget, 2019). In this story, firstly, I share my thoughts about social justice from a care ethics perspective, reflecting on the ideas of moral philosopher Margaret Urban Walker (1998, 2007). To her, social justice is a practice of responsibility in relationships. Secondly, I reflect on visual art as a medium in my art therapy practice and my PhD project inspired by German artist Joseph Beuys, and art therapist and researcher Shaun McNiff. To them, art is ahead of-, and challenging societal conventions, making way to new -so called- social sculptures. This story is a quest of visual art being a medium to connect and built relationships.